2015
DOI: 10.3390/ijms16059625
|View full text |Cite
|
Sign up to set email alerts
|

A Fusion Protein of RGD4C and β-Lactamase Has a Favorable Targeting Effect in Its Use in Antibody Directed Enzyme Prodrug Therapy

Abstract: Antibody directed enzyme prodrug therapy (ADEPT) utilizing β-lactamase is a promising treatment strategy to enhance the therapeutic effect and safety of cytotoxic agents. In this method, a conjugate (antibody-β-lactamase fusion protein) is employed to precisely activate nontoxic cephalosporin prodrugs at the tumor site. A major obstacle to the clinical translation of this method, however, is the low catalytic activity and high immunogenicity of the wild-type enzymes. To overcome this challenge, we fused a cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Immunofluorescent staining of fluorescein isothiocyanate-RGD4CβL and a binding assay of 99m Tc-RGD4CβL confirmed the affinity and specificity of RGD4CβL on tumor cells, and that the 99m Tc-RGD4CβL exhibited a short half-life in rats. The half-lives of distribution and elimination of 99m Tc-RGD4CβL were 7.8 and 21.9 min, respectively ( 26 ), which are favorable for its use in TEPT. In the present study, in vivo imaging and biodistribution assays using radioiodine labeling technology were performed, and revealed that RGD4CβL may be efficiently labeled with 125 I, and 125 I-RGD4CβL exhibited good stability in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescent staining of fluorescein isothiocyanate-RGD4CβL and a binding assay of 99m Tc-RGD4CβL confirmed the affinity and specificity of RGD4CβL on tumor cells, and that the 99m Tc-RGD4CβL exhibited a short half-life in rats. The half-lives of distribution and elimination of 99m Tc-RGD4CβL were 7.8 and 21.9 min, respectively ( 26 ), which are favorable for its use in TEPT. In the present study, in vivo imaging and biodistribution assays using radioiodine labeling technology were performed, and revealed that RGD4CβL may be efficiently labeled with 125 I, and 125 I-RGD4CβL exhibited good stability in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…While human enzymes are less immunogenic, they are in general nonspecific in targeting tumor cells. Genetic mutation of human enzymes to react with a specific substrate that cannot be activated by wild-type enzymes is one of the solutions . In addition to their broad therapeutic applications, AECs are also useful for target detection .…”
Section: How Are Antibodies Used?mentioning
confidence: 99%
“…Genetic mutation of human enzymes to react with a specific substrate that cannot be activated by wild-type enzymes is one of the solutions. 344 In addition to their broad therapeutic applications, AECs are also useful for target detection. 345 Among various known AECs, some of them have specific target-binding abilities and possess excellent catalytic activities capable of release and amplification of detectable signals.…”
Section: Antibody Conjugatesmentioning
confidence: 99%
“…One example is use of yeast cytosine deaminase (yCD), which converts a non-toxic prodrug, 5-fluorocytosine (5-FC), to the clinically prevalent cytotoxic drug, 5-fluorouracil (5-FU), for the treatment of glioblastoma (Polak et al, 1976; Zhang et al, 2015). Proposed methods for introducing prodrug converting enzymes (PCEs) require the targeted delivery of the enzyme to the cancer, as any off-target activity would kill the benign cell upon addition of the prodrug (Biela et al, 2003; Fong et al, 2011; Tian et al, 2013; Wang et al, 2015). While many methods have tested successful for targeting tumors in vitro , none are completely free of risk and safety concerns.…”
Section: Introductionmentioning
confidence: 99%